Surgical stabilization of canine lateral scapulohumeral luxation using extracapsular tension suture with screws and nylon wire - case report (Veterinária Notícias, 2018)
A dog was consulted with functional disability of the right thoracic limb.Radiographic image showed lateral luxation of the scapulohumeral joint.The animal was submitted to surgical treatment using tension suture withscrews and Nylon wire, with satisfactory result and functional use of thelimb 30 days postoperatively.